Anti-inflammatory, anti-nociceptive and sedative-hypnotic activities of lucidone D extracted from Ganoderma lucidum - Feng, Xia; Wang, Yan (Cellular and Molecular Biology, 2019)
Inflammation and insomnia are two types of symptoms very likely occur in life, seriously perplexing people’s work and life. How to alleviate these symptoms is an urgent medical problem. Lucidone D (LUC) is a terpene from the ethanol extract of Ganoderma lucidum fruiting body. Triterpenoids are also the main pharmacological components of Ganoderma lucidum. In recent years, people pay more and more attention to its anti-inflammatory effect. In this study, LPS induced RAW264.7 macrophage inflammatory response model was used to evaluate the anti-inflammatory activity of LUC. The results showed that LUC could significantly inhibit the production of inflammatory mediators NO, which may play a role by down-regulating the expression level of iNOS and COX-2 proteins. Meanwhile, the production of TNF-Î± and IL-6 was significantly inhibited. These results indicate that LUC has obvious anti-inflammatory activity. Writhing and sedation tests in ICR male mice showed that LUC showed significant analgesic and sedative effects. In conclusion, these results suggest the anti-inflammatory, analgesic and sedative effects of LUC in vitro and in vivo.